KAJIAN PERSEBARAN SPASIAL KUALITAS AIR SUNGAI KARANG MUMUS, SAMARINDA, KALIMANTAN TIMUR - Vita Pramaningsih; Slamet Suprayogi; Ig. L. Setyawan Purnama (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Problem of river pollution caused domestic waste human activity as residences, home industries and market. Karang Mumus River is Subwatershed Mahakam through Samarinda City. Purpose of this research is to analysethe spatial distribution of Karang Mumus River pollution, namely BOD, COD and TSS. Method used field survey, water sampling each river segment, laboratory analysis and make spatial distribution of pollution by ArcGIS application. Result of this research is to find the highest BOD, COD and TSS content on the residence side especially in flood plain area, home industries of tofu-tempeh and urban activity such as market, hospital, and Mall. Spatial distribution of BOD and COD find upstream and downstream has high content, then TSS hight content find in downstream area. Dominant activity in upstream area are home industries tofu-tempeh and in the downstream area are many residence in the flood plain area with their activity and also urban area.